Mapping of the Fabaceae Family Field Laboratory on Mount Galunggung as a Learning Media - Indriani, Yayu Azmi; Hernawati, Diana; Putra, Rinaldi Rizal (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
This study aims to make a mapping of the field laboratory of Fabaceae plants on Mount Galunggung as a learning medium. This study uses an exploratory qualitative method with a survey technique which is divided into 3 research stations based on their altitude, namely Station 1 (600 – 800 meters above sea level), Station 2 (800 – 1000 meters above sea level), and Station 3 (1000 – 1200 meters above sea level). The stages of this study include planning and preparation, implementation, data collection, and data analysis. The results of the study showed that there were 2 sub-families, 5 genera, 6 types of Fabaceae families in Mount Galunggung. The most dominating sub-family in the Mount Galunggung area is the sub-family Caesalpinioideae with a percentage of 93%. Mount Galunggung is an ideal place to be used as a field laboratory to study Fabaceae plants presented in the form of digital and analog maps processed using ArcGIS and Google Earth Pro technology.ABSTRAK: Penelitian ini bertujuan untuk membuat pemetaan laboratorium lapangan tumbuhan familia Fabaceae di Gunung Galunggung sebagai media pembelajaran. Penelitian ini menggunakan metode kualitatif eksploratif dengan teknik survey yang terbagi ke dalam 3 stasiun penelitian berdasarkan ketinggiannya yaitu Stasiun 1 (600 – 800 mdpl), Stasiun 2 (800 – 1000 mdpl), dan Stasiun 3 (1000 – 1200 mdpl). Tahapan pada penelitian ini meliputi perencanaan dan persiapan, pelaksanaan, pengumpulan data, dan analisis data. Hasil penelitian menunjukan adanya 2 sub-familia, 5 genus, 6 jenis familia Fabaceae di Gunung Galunggung. Sub-familia yang paling mendominasi di Kawasan Gunung Galunggung adalah sub-familia Caesalpinioideae dengan presentase 93%. Gunung Galunggung menjadi tempat ideal digunakan sebagai laboratorium lapangan untuk mempelajari tumbuhan familia Fabaceae yang disajikan dalam bentuk peta digital dan analog yang diolah menggunakan teknologi ArcGIS dan Google Earth Pro.